Crack tip field in circumferentially-cracked round bar (CCRB) in tension affected by loss of axial symmetry - J. Toribio; B. González; J.C. Matos (Fracture and Structural Integrity)
In this paper, the stress intensity factor (SIF) is computed in a circumferentially-cracked round bar (CCRB) subjected to tensile loading, considering that the resistant ligament is circular and exhibits certain eccentricity in relation to the cylinder axis. The computation was performed by means of the finite element method (FEM) using a three dimensional (3D) model and the J-integral, the analyzed variable being the eccentricity of the circular ligament. Results show that the SIF is higher at the deepest point of the crack and that an increase of eccentricity (in relation to the bar axis) raises the difference between the SIF values along the crack front. From a certain value of the misalignment a bending effect appears, so that the crack remains closed in the area near the point of lower depth.